Atividade antidepressiva de agentes antioxidantes em um modelo animal de depressão resistente a antidepressivos - Gomes, Patricia Helena Zanier [UNIFESP] (2008)
as a genetic predisposition component. Concerning environmental factors, social isolation seems to increase antidepressant resistence in depressive patients. Thus, social isolation could be used to develop an animal model of antidepressant resistent depression. In parallel, the main antidepressant agents in current clinical use (MAO inhibitors and monoamine reuptake inhibitors) share the ability of directly or undirectly avoiding monoamine oxidation by MAO therefore also avoiding the production of free radicals. The aims of the present study were twofold: first, to develop an animal model of antidepressant resistent depression comprising both the environmental component and the genetic predisposition component; second to investigate the effects of repeated treatment with the association of the antioxidant agents vitamins C + E on such a model. In experiment 1 we demonstrated that social isolation for 6h (but not for 1 or 12h) increased immobility duration in the forced swim test (FST). In experiment 2 we showed that mice which presented higher immobility duration in the first session of the FST continue to present higher depressive behavior in the following tests. In addition, we showed that this higher basal depressive behavior could be further increased by social isolation. Thus, we could classify the animals in four groups: mice with lower predisposition to depressive behevior which were not submitted to social isolation (pouco deprimido–não isolado: PNão group), mice with lower predisposition to depressive behavior which were submitted to social isolation (pouco deprimido–isolado: PIso group), mice with higher predisposition to depressive behavior which were not submitted to social isolation (muito deprimido– não isolado: MNão group) and mice with higher predisposition to depressive behavior which were submitted to social isolation (muito deprimido–isolado: MIso group). In experiment 3 we showed that differences in depressive behavior among the 4 groups were not related to motor function alterations since no difference was observed in the open-field test. In experiments 4-8 we showed that fluoxetine or amitriptiline long-term treatments were effective in decreasing immobility duration only in the MNão group, suggesting that immobility durations presented by the PNão and the PIso groups reflect a non-pathological (reactive) depressive behavior, whereas the immobility duration presented by the MIso group models an antidepressant resistent pathological depression. In experiment 9 and 10 we showed that long term treatment with vitamins C + E significantly reduced depressive behavior in both MNão and MIso groups, suggesting the clinical potential of such treatment for antidepressant resistent depression. In experiment 11 we demonstrated that the pro-oxidant agents aminotriazole and 3-nitropropionic acid were not able to increase depressive behavior in mice without genetic predisposition to depressive behavior. Finally, experiment 12 showed that both the increase in depressive behavior produced by social isolation or by higher depressive behavior predisposition and the antidepressive behavior produced by antioxidant treatment in the MIso group are not associated with hypocampal lipid peroxidation but are associated with alterations in plasmatic corticosterone levels. In conclusion, in the present study we have developed an animal model of antidepressant resistent depression which is sensitive to antioxidant long-term treatment. These findings strengthen the involvement of oxidative stress in the pathophysiology of depression and suggest the clinical potential of antioxidant agents to treat antidepressant resistent depression.